Heterogeneous photocatalysis applied to indoor building material: towards an improved indoor air quality - Yu, Q. L. (2011)
In the present article, kinetics of the photocatalytic oxidation (PCO) of nitric oxide (NO, as a typical air pollutant) is addressed. An extended Langmuir-Hinshelwood reaction rate model is proposed to describe the PCO of NO under indoor air conditions. The derived model incorporates the influence of the indoor air conditions in the process of the PCO. The good agreement between the predictions from the model and experimental results indicates the validity of the proposed model.